Impacto del cambio climático en las cadenas productivas del café y cacao: Presentation at ExpoCafé 2016 - Lima, Peru - Lundy, Mark M.; Bunn, Christian (2016)
What is the projected impact of climate change on coffee and cocoa value chains globally and in Peru. What can be done to improve the resilience of these production systems to the projected impact of climate change?